A Review of Pickering Emulsions: Perspectives and Applications - Fernanda Brito de Carvalho-Guimarães; Kamila Leal Correa; Tatiane Pereira de Souza; Jesus Rafael Rodríguez Amado; Roseane Maria Ribeiro-Costa; José Otávio Carréra Silva-Júnior (MDPI AG, 2022)
Pickering emulsions are systems composed of two immiscible fluids stabilized by organic or inorganic solid particles. These solid particles of certain dimensions (micro- or nano-particles), and desired wettability, have been shown to be an alternative to conventional emulsifiers. The use of biodegradable and biocompatible stabilizers of natural origin, such as clay minerals, presents a promising future for the development of Pickering emulsions and, with this, they deliver some advantages, especially in the area of biomedicine. In this review, the effects and characteristics of microparticles in the preparation and properties of Pickering emulsions are presented. The objective of this review is to provide a theoretical basis for a broader type of emulsion, in addition to reviewing the main aspects related to the mechanisms and applications to promote its stability. Through this review, we highlight the use of this type of emulsion and its excellent properties as permeability promoters of solid particles, providing ideal results for local drug delivery and use in Pickering emulsions.